Fabrication of digital linear expansion experiment set based on the ATMEGA328 microcontroller - Nofsi Meiza; Yulkifli Yulkifli; Zulhendri Kamus (Department of Physics – Universitas Negeri Padang UNP, 2017)
Development of science and technology can’t be separated from physics. Basically physics is born and grow doing by experiments. For more accurate results of the research, required experiments with the level of high accurate. In the laboratory, experimental linear expansion is analog. Results of analog eksperiment has an error. This research has purpose for determine the performance specifications and desain of digital microcontroller atmega328. Based on research results obtained, first meansure of experiments digital linear expasion process in output sensor and changing obtained with the expected output. Result of experiment digital is displayed with LCD. Sensor used is LM35 temperature sensor of metal, brass, and iron. Second, experiment digital for linear expansion has the percentage of precision in brass, iron, and aluminum respecteli is 97.58%, 95.92%, and 97.98%. While for precision is 0.97, 0.95, and 0.97